The effect of leadership sense giving and cognitive flexibility on team adaptive performance - Passos, A. M.; Sousa Guedes, A.; Santos,C.M.; Uitdewilligen, S.; Maynard, M.T. (19th EAWOP Congress, 2019)
Purpose: The number of publications that aimed to explain team adaptation has increased in the last years. Authors have argued that in order to adapt to unexpected situations, teams need to adjust their cognitive and behavioural processes, and emergent states. This study clearly goes beyond previous research by experimentally testing effect of leadership sense giving and team cognitive flexibility on team adaptive performance. Design/ Methodology: We conducted a laboratory experiment using a 2 x 2 between subject design. Each three-person teams (total: N = 63 teams; 189 undergraduate students) worked on a computer-based real-time command-and-control fire fighting simulation (NFC) for approximately 1 hour and a half. Results: Findings suggest that the cognitive flexibility manipulation has an effect on team adaptive performance. Results also suggested an interaction effect between cognitive flexibility and leadership sense giving. Limitations: These were ad-hoc teams that just worked together in the lab on this particular task. Research/ Practical Implications: This study offers meaningful contributions to team cognition literature by showing that the team’s capacity to be flexible and leadership sense giving are crucial to achieve high levels of performance in dynamic environments. Originality/ Value: This study opens a new avenue on team cognition literature by showing that team adaptation is stronger for teams in the cognitive flexibility condition, than for teams in the control condition. The innovative power of this study lies in the manipulation of a cognitive variable and leadership functions that have been scarcely used in team literature.